Construção de um algoritmo para prevenção de prolapso em estomias intestinais - Santos, Alberto Matos dos (2022)
Introduction: Intestinal ostomy is a surgical procedure that aims to divert the normal path of fecal effluents, which can be permanent or temporary. As with any surgery, colostomies and ileostomies can trigger complications, among which prolapse stands out, which may be related to the surgical technique used, as well as the absence of preoperative stoma demarcation, among other intrinsic factors. In this context, Afaf Meleis' Theory of Nursing Transitions and Nola Pender's MPS are fundamental for understanding transitional processes and cognitive processes that stimulate health-promoting behaviors. Objectives: To build an algorithm for prolapse prevention in intestinal ostomies; Identify the main nursing care related to the prevention of prolapse in intestinal ostomies; Analyze the algorithm from Nola Pender's MPS metaparadigms and variables. Method: The integrative review used LILACS, SciELO, BDENF, PubMed via MedLine and CINAHL databases. The PICO strategy was shared in a Google Forms form, which enabled simultaneous contribution through the Rayyan QCRI program, with selected studies published between 2011 and 2020 in the field of Stomatherapy. The descriptors used for the search were: ostomy, colostomy, nursing care and prolapse. After the construction of the integrative review, a methodological study with a qualitative approach was carried out, which culminated in the construction of an algorithm. Results: The integrative review resulted in a final sample of 22 articles about nursing care, of which preoperative education and stoma demarcation stood out. The final version of the algorithm included four versions, the last one being improved by a graphic design professional regarding the quality of the content and visual identity, whose nursing care was divided into three stages: pre, trans and postoperative. In the meantime, after the construction of the algorithm, the metaparadigms and variables of Nola Pender's MPS were discussed, emphasizing some aspects and contexts considered relevant during its elaboration, with the aim of clarifying the reader's understanding of nursing care itself and its correlation with the points of care and services offered from the perspective of the RCPD. Conclusion: the objectives were achieved, as it built an algorithm with accessible language and a bold design, aligned with the needs and demands of the person with an ostomy throughout the perioperative period, with an emphasis on preoperative education, demarcation of the stoma, as well as, revealed the need for a Network Care Protocol, including the presence of the stomatherapist at each level of care, which must be linked to the Care Service for the Ostomized Person with a focus on the proper use of devices and adjuvants, access to the adapted bathroom, manual reduction of stoma, stoma self-management programs, home visits and telephone follow-up by the stomatherapist.